1977
DOI: 10.1163/26660644-04602011
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation between Movements and the Shape of Somites in Early Embryos of the Teleost Brachydanio Rerio

Abstract: As a working hypothesis it is supposed that in the teleost Brachydanio rerio, the muscle contractions, the growth, and probably some other factors, cause the first changes in the shape of the somites. Furthermore, the movements of the embryo could yield the forces by which the somites are brought to their theoretically optimal shape.In order to test this hypothesis, we investigated the somite shape and structure of spontaneously immobile embryos. Although the results are difficult to interpret, they certainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Interestingly, it has been shown that the angle of inflection of chordate myomeres is related to function (Van Der Stelt 1968). The angle of inflection in the conodonts (80"-90") is similar to values measured in teleost larvae (Van Raamsdonk et a/. 1977) but greater than angles in Branchiostorna (60°-70").…”
Section: Trunk Musculaturesupporting
confidence: 76%
“…Interestingly, it has been shown that the angle of inflection of chordate myomeres is related to function (Van Der Stelt 1968). The angle of inflection in the conodonts (80"-90") is similar to values measured in teleost larvae (Van Raamsdonk et a/. 1977) but greater than angles in Branchiostorna (60°-70").…”
Section: Trunk Musculaturesupporting
confidence: 76%
“…Microscopic, immunological, and histochemical examination reveals a greater diversity of fish muscle fiber types. The myotome of the adult zebrafish is composed of five distinguishable layers of muscle cells: 1) the superficial adult red layer, 2) the intermediate pink layer, 3) the deep white layer, 4) the scattered dorsal and ventral fiber layer, and 5) the red muscle rim layer (Van Raamsdonk et al 1978, 1980, 1982aWaterman 1969). At one extreme, superficial red fibers have small diameters, contain many mitochondria, have a rich blood supply, and have metabolic specializations, making them suitable for sustained activity but not rapid contractions.…”
Section: Introductionmentioning
confidence: 99%
“…At a physiological level, the first movements (17 h) (Saint-Amant and Drapeau 1998) are observed shortly after neuromuscular innervation commences (Liu and Westerfield 1992), which is when muscle contractile properties emerge (Van Raamsdonk et al 1977). Muscle pioneers are the first fibers contacted by primary motoneurons, the first to form functional synapses, and the first to contract (Melancon et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of individual myotomes and the orientation of muscle fibres varies between elasmobranches, primitive and advanced teleosts, along the length of the body and during development (van der Stelt, 1968;Alexander 1969;Raamsdonk, 1977). In both elasmobranchs and teleosts all but the most superficial fibres make varying angles up to 40° with the longitudinal axis of the body (van der Stelt, 1968;Alexander, 1969).…”
Section: Fast White Musclesmentioning
confidence: 99%